Relationship Between Impulsivity, Sensation-Seeking, and Drug Use in Aggressors and Victims of Violence - Molero Jurado, María del Mar; Pérez-Fuentes, María del Carmen; Simón Márquez, María del Mar; Barragán Martín, Ana Belén; Sisto, Maria; Gázquez Linares, José Jesús (Frontiers in Psychology, 2020)
Introduction: The impulsivity, sensation-seeking and drug use variables, in addition to being closely related, have repercussions on peer conflict and violence in schools. Objetive: The purpose of this study was to analyze the relationship between impulsivity, sensation-seeking, and drug use in aggressors and victims of violence. Methods: The study design was cross-sectional and observational. The study sample was made up of 822 students aged 13 to 18 who had completed an ad hoc questionnaire, the State Impulsivity Scale and the Sensation-Seeking Scale. Results: The results showed that the aggressors had high levels of gratification, automatism, attentional factor, disinhibition, and susceptibility to boredom and used alcohol and/or tobacco. Conclusions: The design of an effective education intervention for reducing risk behaviors related to violence must focus on these variables.